Quantitative super-resolution microscopy reveals the differences in the nanoscale distribution of nuclear phosphatidylinositol 4,5-bisphosphate in human healthy skin and skin warts - Hoboth, Peter; Sztacho, Martin; Quaas, Alexander; Akgül, Baki; Hozák, Pavel (Frontiers in Cell and Developmental Biology, 2023)
Imaging of human clinical formalin-fixed paraffin-embedded (FFPE) tissue sections provides insights into healthy and diseased states and therefore represents a valuable resource for basic research, as well as for diagnostic and clinical purposes. However, conventional light microscopy does not allow to observe the molecular details of tissue and cell architecture due to the diffraction limit of light. Super-resolution microscopy overcomes this limitation and provides access to the nanoscale details of tissue and cell organization. Here, we used quantitative multicolor stimulated emission depletion (STED) nanoscopy to study the nanoscale distribution of the nuclear phosphatidylinositol 4,5-bisphosphate (nPI(4,5)P2) with respect to the nuclear speckle (NS) marker SON. Increased nPI(4,5)P2 signal were previously linked to human papillomavirus (HPV)-mediated carcinogenesis, while NS-associated PI(4,5)P2 represents the largest pool of nPI(4,5)P2 visualized by staining and microscopy. The implementation of multicolor STED nanoscopy in human clinical FFPE skin and wart sections allowed us to provide here the quantitative evidence for higher levels of NS-associated PI(4,5)P2 in HPV-induced warts compared to control skin. These data expand the previous reports of HPV-induced increase of nPI(4,5)P2 levels and reveal for the first time the functional, tissue-specific localization of nPI(4,5)P2 in NS in clinically relevant samples. Moreover, our approach is widely applicable to other human clinical FFPE tissues as an informative addition to the classical histochemistry.